A Study on impact of Job Motivation, Satisfaction and performance on Employee engagement in higher educational Institute. - ARORA, MANVI; KAUR, AVJEET (International Journal of Psychosocial Rehabilitation, 2020)
Engaged employees are the pillars of any successful organizations . They are the major contributors for financial and market success of any organization . They give eminent performances by trying to reach next level of success and continuously striving to perform and set new standards of excellence in the assigned task. Globally enhancing employee engagement has made significant impact in business organizations. Employee engagement creates healthy work culture and communication practices, if employees get a platforms to express their concerns and opportunities to grow and develop their potential. Organizations high on their achievements ae aware that employees motivation ,satisfaction and performance are the most important elements of employee engagement. This study is based to examine the factors that contributes tothe satisfaction level of employee to name a few are fit at the job, good communication, appreciation level and clear objectives.. Finally, this study discusses employee engagement and its various aspects of definitions, organizational success, and how to develop a successful employee engagement practice effectively and efficiently .